Working from home, wages, and regional inequality in the light of COVID-19 - Michael Irlacher; Michael Koch (Johannes Kepler University of Linz, Department of Economics, 2020)
We use the most recent wave of the German Qualifications and Career Survey and reveal a substantial wage premium in a Mincer regression for workers performing their job from home. The premium persists within narrowly defined jobs and after controlling for workplace activities and accounts to more then 10%. In a next step, we provide evidence on substantial regional variation in the share of jobs that can be done from home across NUTS2 districts in Germany. Our results suggest that the COVID-19 crisis might affect already poorer regions more heavily as a lower share of workers can work from home there. Hence, looking at regional disparities in terms of different types of occupations is central for policy makers in choosing the right economic policies to mitigate the consequences of the crisis.
Keywords: J31; J22; J61; R10; 330; Working from home; COVID-19; Regional disparities; Home office; BIBB-BAuA